The Macroeconomic and Sectoral Performance of Housing Supply Policies in Selected MENA Countries : A Comparative Analysis - Baharoglu, Deniz; Peltier, Nicolas; Buckley, Robert (World Bank, Washington, DC, 2021)
This paper analyzes housing sector policies and their effects on macroeconomic and sectoral performance in a number of Middle East and North African (MNA) countries. Some of these countries confront very rapid growth in their labor forces, others are now experiencing the world’s highest rates of urbanization. In such countries, the spill-over effects of housing policy on labor markets, savings behavior, factor productivity, and ultimately the quality of economic growth are important. Similarly, policies that cause housing costs to rise for the entire population can have a greater effect on the poor than do direct housing subsidy programs. In short, untangling the effects of housing policy requires a broad sectoral perspective. Accordingly, the analysis examines these broader issues, even though the focus remained on how policies could improve the situation of the poor.